2017
DOI: 10.4082/kjfm.2017.38.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Carboxymethylcellulose and Hyaluronate in Dry Eye Disease: A Systematic Review and Meta-Analysis

Abstract: BackgroundThe efficacy of two artificial tears, carboxymethylcellulose (CMC) and hyaluronate (HA), was compared in the treatment of patients with dry eye disease.MethodsWe conducted a systematic review and meta-analysis on randomized controlled trials in the PubMed, Embase, Cochrane Library, and ClinicalTrials.gov databases. The efficacy was compared in terms of the mean change from baseline in tear break-up time. The meta-analysis was conducted using both random and fixed effect models. The quality of the sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 16 publications
0
23
2
Order By: Relevance
“…We also reviewed the latest published meta-analysis that focused on DED therapy. In summary, in comparison to AT or placebo, 0.05% cyclosporine group and omega-3 group had lower OSDI (MD = 4.10 and MD = 0.968), but carboxymethylcellulose group and sodium hyaluronate group had no statistical significance [20][21][22][23]. In consideration of the fact that AS group had significant lower OSDI (MD = 10.75) than AT group, AS might had powerful effectiveness in comforting DED patients.…”
Section: Discussionmentioning
confidence: 89%
“…We also reviewed the latest published meta-analysis that focused on DED therapy. In summary, in comparison to AT or placebo, 0.05% cyclosporine group and omega-3 group had lower OSDI (MD = 4.10 and MD = 0.968), but carboxymethylcellulose group and sodium hyaluronate group had no statistical significance [20][21][22][23]. In consideration of the fact that AS group had significant lower OSDI (MD = 10.75) than AT group, AS might had powerful effectiveness in comforting DED patients.…”
Section: Discussionmentioning
confidence: 89%
“…In a recent review, Song et al carried out a meta-analysis of five original studies comparing CMC and HA eye drops. 13 The authors concluded that CMC was more efficacious than HA in treating DED. These conclusions, however, are obviously limited, since they were based on nonsignificant results and only TBUT test results were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Its etiologies include causes secondary to systemic autoimmune disorders such as Sjogren's syndrome, rheumatoid arthritis, systemic lupus erythematous, and so on that are bothersome to doctors and patients [6][7][8][9][10]. In conventional treatment, arti cial tear eye drops are mainly used to moisturize the ocular surface and offer additional lubrication [11]. To address symptoms of chronic in ammation, antiin ammation and topical immunosuppression agents could be considered [12].…”
Section: Introductionmentioning
confidence: 99%